Correlations of chemokine CXCL16 and TNF-α with coronary atherosclerotic heart disease - Xing, Jieyong (Exp Ther Med, 2018)
This study determined the correlations of CXC ligand 16 (CXCL16) and tumor necrosis factor-α (TNF-α) levels with coronary atherosclerotic heart disease (CAHD) and screened for new clinical markers for the prognosis and treatment of the disease. Eighty patients with coronary heart disease and 50 healthy subjects were enrolled into a CAHD or healthy control group, respectively. Computed tomography (CT) coronary angiography and Gensini integral were used to classify plaques and evaluate patients with coronary heart disease. The serum levels of CXCL16 and TNF-α of subjects in each group were detected by enzyme-linked immunosorbent assays (ELISA), and the correlation between levels and clinical markers (such as blood pressure, glucose, lipid and heart rate) and the severity of disease were analyzed. Our results showed the serum levels of CXCL16 and TNF-α were significantly higher in the CAHD group than those in the CK group. The serum CXCL16 levels of the CAHD group patients with plaques were distinctly higher than those of the CADH group patients without plaques, but there were no significant difference in serum TNF-α levels between these two groups of patients. The level of CXCL16 had a significantly positive correlation with the severity of disease, but there was no significant correlation between TNF-α level and the severity of disease. Also, there was no significant correlation between the CXCL16 levels and blood pressure, blood glucose, heart rate, total cholesterol, triglyceride or high-density lipoprotein cholesterol, but there was a clear correlation with the low-density lipoprotein cholesterol. Finally no significant correlations were found between TNF-α levels and each of the clinical markers studied. Based on our findings, the levels of CXCL16 and TNF-α in the patients with coronary heart disease were abnormally increased and the level of CXCL16 correlated closely with the severity of disease. These markers seem to be reliable biological markers for prognosis and disease evaluation in coronary heart disease patients.